Opportunity Cost in Monetary Donation Decisions to Non-identified and Identified Victims - Moche, Hajdi; Erlandsson, Arvid; Andersson, David; Västfjäll, Daniel (Frontiers in Psychology, 2020)
Do people consider alternative uses of money (i.e. opportunity cost) when asked to donate to a charitable cause? To answer this question, we examined the effect of providing versus not providing participants with an opportunity cost reminder when they are asked to donate money to causes with identified and non-identified victims. The results of two studies show that when making one-time donation decisions, people become less willing to donate to charity when reminded of opportunity cost, but mainly for non-identified victims. Moreover, framing the opportunity cost reminder as prosocial versus proself did not influence willingness to donate. Overall, our evidence suggests that opportunity cost reminders influence people’s donation behavior depending on whether charities identify supported victims or not.